(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The etiology and pathogenesis of PRS remain unclear. Many works in this direction did not change the situation. However, ideas about the pathogenesis of PRS have recently undergone significant changes, primarily due to advances in the field of clinical immunology of ENT diseases. In all theoretical views on the genesis of nasal polyps, the involvement of the immune system, especially the immune status of the nasal mucosa, plays a leading role.